(untitled) (Herald of Journalism, 2018)
The article considers the stages of preparation for public speaking. The preparation for the performance is a very important and responsible business in the activities of the creative person. The relevance of the research topic due to the fact that the modern world, with the rapid development of media and communications, has dramatically increased the interest in rhetoric. The skill of public speaking, the art of debate and communication in any society is the key to popularity, recognition, leadership, self-fulfillment and a higher level of life. The characteristic of public speech is given in this article, the special of public speech are consided. This perspective has many sided character. It conveys an attempt to determine a place of public speech in the stylistic system of Kazakh language and gives some notes on usage of polite forms, vocabulary, phrase construction and some techniques of modern rhetoric in high-level spoken public speech. Key words: speaker, speech, oratory, public speaking, creative person.